Bypass Procedure Performed in the Field of a Decompressive Craniectomy in the Case of an MCA Dissecting Aneurysm: Case Report and Review of the Literature - Bartoš, Robert; Lodin, Jan; Hejčl, Aleš; Humhej, Ivan; Concepción, Ingrid; Cihlář, Filip; Sameš, Martin (Brain sciences, 2020)
Treatment of complex aneurysms often requires additional surgical tools including the use of the extra-intracranial (EC-IC) bypass. The following report depicts the utilization of the EC-IC bypass in treating a dissecting aneurysm several hours after a salvage emergent evacuation of an acute subdural hematoma via decompressive craniectomy (DC). Preserving the superficial temporal artery during the DC provided a donor artery for the bypass surgery.